Analisis Penggunaan Gadget terhadap Kemampuan Interaksi Sosial pada Anak Usia Dini - Putri Hana Pebriana (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
Technological developments increasingly sophisticated and growing. This leads to various influences of human lifestyle both mindset and behavior. One of the technological developments that affect the human mind is the gadget. Gadgets are media used as a means of modern communication. Gadgets not only affect the mindset or behavior of adults, but also affect the behavior of young children. In essence, early childhood tend to be happy with new things that he got through the activity by playing. Playing is fun for the kids, with children's play can explore all the potential. The majority of children in Indonesia spend time playing with gadgets. Surely this affects the development of children, especially in the development of social interaction. Social interactions can be interpreted as relationships that occur within induvidu groups are interconnected both in communication and social action. The purpose of this study to describe the use of gadgets to the ability of social interaction of early childhood. The research method used in this study is literature review is by connecting research with existing literature and fill the gap in previous research. The results obtained in this study is the use of gadgets most children use it to play. From these small things, children who initially love to play with their friends can change with the usual given a gadget as a substitute for playmates.